Management of bladder stones: the move towards non-invasive treatment (Faculty of Medicine Universitas Indonesia, 2017)
Background: Bladder stone accounts for 5% of all cases of urolithiasis. Bladder stones management has evolved over the last decades from open bladder surgery (sectio alta) to intracorporeal cystholithotripsy as well as extracorporeal shock wave lithotripsy (ESWL). ESWL presents to be a promising modality in the management of bladder calculi due to its simplicity and well tolerability. This study is thus conducted to present data on the safety and effectiveness of ESWL in the management of bladder stone patients. Methods: This is a retrospective study evaluating the medical records of 92 bladder calculi patients admitted to Cipto Mangunkusumo General Hospital (RSCM) from January 2011 to April 2015. Patient's age, gender, type of stone and procedure being done, status of stone disintegration, length of hospital stay, and any complications that may occur are noted down and statistically analyzed using SPSS v. 20. Results: Majority of the patients underwent ESWL (49 out of 92, 53.3%). The stone free rates for ESWL, intracorporeal lithotripsy, and sectio alta are 93.9%, 97.0% and 100% respectively. One patient had to repeat ESWL. The ESWL group had the smallest stone size average compared to the intracorporeal lithotripsy and section alta group (2.5 cm±2.0 cm vs 4.8 cm±3.7 cm vs 7.4 cm±5.4 cm respectively). The ESWL sessions were conducted in the outpatient clinic, and thus no hospital stay was required. Conclusion: ESWL can be suggested as an effective non-invasive approach in the disintegration of bladder stone of ≤25 mm with a promisingly high stone-free rate (93.9%) Furthermore, ESWL can be performed on an outpatient basis with minimal complications.